2015
DOI: 10.1590/s1517-707620150001.0015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficiência de sistemas de proteção de superfície para concreto: absorção de água, migração de cloretos e ângulo de contato

Abstract: RESUMOA camada de cobrimento do concreto funciona como uma barreira natural ao ingresso de agentes agressivos para o interior do material, dificultando a penetração de íons cloretos, reduzindo a absorção de água e limitando o acesso de oxigênio. Para garantir a eficiência desta camada protetora o uso de tratamentos de superfí-cie mostra-se como uma alternativa viável para prolongar o período de proteção proporcionado pelo cobrimento do concreto. O objetivo deste trabalho é estudar o efeito de proteção de quatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Then, the chloride penetration and the chloride migration tests on saturated concrete do not test or simulate the strength of activity of this product, although the hydrophobic agent has presented 13% of reduction in chloride diffusion coefficient. Medeiros et al (2015) showed in their work, the use of goniometry technique for testing the hydrophobic capacity to increase the contact angle of water with the treated substrate, reducing the affinity for water.…”
Section: Fig 5 Presents the Results Of Chloride Diffusion Coefficienmentioning
confidence: 99%
“…Then, the chloride penetration and the chloride migration tests on saturated concrete do not test or simulate the strength of activity of this product, although the hydrophobic agent has presented 13% of reduction in chloride diffusion coefficient. Medeiros et al (2015) showed in their work, the use of goniometry technique for testing the hydrophobic capacity to increase the contact angle of water with the treated substrate, reducing the affinity for water.…”
Section: Fig 5 Presents the Results Of Chloride Diffusion Coefficienmentioning
confidence: 99%
“…Representing one of the most important parameters of concrete durability, capillary suction is one of the transport mechanisms related to the entry of harmful substances into concrete, with particularly damaging effects in areas where there are alternating climatic conditions of wetting and drying [ 52 ]. During these cyclic processes, there is absorption of water with damaging substances in solution, then when the water evaporates those substances are kept inside the concrete, increasing its concentration after each successive cycle [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Estes materiais podem ser classificados entre formadores de película, hidrofugantes de superficie e bloqueadores de poros. Em todos os casos, o objetivo é reduzir a entrada de agentes por migração, difusão ou absorção por capilaridade (Medeiros, Leal, et al, 2015;Medeiros, Pereira, et al, 2015). (Suleiman et al, 2014) avaliam o uso destes materiais em amostras de concreto sujeitas ao ataque físico por sulfatos, de forma a verificar se é possível aumentar a durabilidade das matrizes.…”
Section: Introductionunclassified
“…Para tanto, optou-se por uma metodologia acelerada de penetração de sulfatos, de forma a permitir a avaliação de desempenho em um curto período de tempo. Tal metodologia baseia-se na migração de íons sulfatos (Brekailo, 2020), de forma similar ao realizado na avaliação de protetores de película em amostras cimentícias expostas à cloretos (Medeiros, Leal, et al, 2015;Medeiros, Pereira, et al, 2015). O protetor de superficie escolhido é do tipo hidrofugante de superficie.…”
Section: Introductionunclassified